VDUP1 potentiates RAS-mediated angiogenesis via ROS production in endothelial cells - Piao, Z H; Yoon, S R; Kim, M S; Jeon, J H; Lee, S H; Kim, T D; Lee, H G; Bae, K H; Min, J K; Chung, S J; Kim, M; Cho, Y S; et al. (Cellular and Molecular Biology, 2009)
Vitamin D3 up-regulated protein 1 (VDUP1) is a tumor suppressor of which expression is reduced in a variety of cancer cells, and enforced expression inhibits the tumor cell proliferation. It inhibits the activity of thioredoxin, thus contributing cellular ROS generation. Since ROS is a critical factor for angiogenesis, we investigated the role of VDUP1 in angiogenesis and endothelial proliferation. The expression of VDUP1 was upregulated by overexpression of an oncogene, Ras. Enforced expression of VDUP1 increases ROS production and proliferation of Ras-overexpressing endothelial cells. Overexpression of VDUP1 increases the resistance to the anchorage-dependent cell death and tube formation of the Ras-overexpressing endothelial cell. In addition, the removal of ROS by ROS scavenger attenuates the effect of VDUP1 on tube formation. These results suggest that VDUP1 is involved in Ras-mediated angiogenesis via ROS generation in endothelial cells.